TYPE AND MEANING OF THE FIGURATIVE LANGUAGE FOUND IN NIKI’S SELECTED SONGS' LYRICS - Wenny Alfiyani (Universitas Aki, 2021)
Abstract Alfiyani, Wenny. 2021. Type and Meaning The Figurative Language Found in Niki Zefanya’s Selected Songs' Lyrics And its Contribution To Teaching Poetry. Final project English Study Program, Faculty of Language and Arts Educations, University of PGRI Semarang. This final project is based on the study, which attempted to the analysis of the Figurative language in Niki – Nicole Zefanya selected songs and its contribution to teaching poetry. The three songs were Lose, Indigo,and La La Lost You. The main purpose of this study was to found the types, the dominations, and the meaning of figurative languages used in the three songs, and also the contribution to teach poetry. This study expected to be a source for the English teachers to teach Poetry. This study is qualitative research, which analyzed the types and meaning of the figurative language found in Niki’s songs lyrics using Kennedy, X.J. and Gioia. D.’s theory (2005). The data of the research were collected by listening, watching, reading, identifying, analyzing, and classifying. The result of the study was there were seven types of figurative language found in the study. And they were metaphor hyperbole repetition simile apostrophe paradox allegory. The contributions of this by using songs lyrics to teaching poetry was could make a positive, relax, and full attention learning, more focus and absorb the material, bringing a sense of community, Improving memory, and enhance their imagination.